2018
DOI: 10.15252/embj.201899978
|View full text |Cite
|
Sign up to set email alerts
|

A wobbly road to drug resistance in melanoma: tRNA ‐modifying enzymes in translation reprogramming

Abstract: Alterations in transcript‐specific translation are emerging as a driver of cellular transformation and cancer etiology. A new study provides evidence for enhanced codon‐dependent translation of hypoxia‐inducible factor 1α in promoting glycolytic metabolism and drug resistance in melanoma cells. This specialized translation reprogramming relies, in part, on mTORC2‐mediated phosphorylation of enzymes modifying the wobble position of the transfer RNA anticodon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Collectively, tRNA thiolation appropriately regulates metabolic outputs by controlling phosphate homeostasis, thereby enabling cells to commit to growth (Figure 8). Intriguingly, this correlation of tRNA thiolation with growth and rewired metabolism is emerging in cancer development (McMahon and Ruggero, 2018; Rapino et al, 2018), suggesting possibly conserved metabolic roles for these modified tRNAs.…”
Section: Discussionmentioning
confidence: 98%
“…Collectively, tRNA thiolation appropriately regulates metabolic outputs by controlling phosphate homeostasis, thereby enabling cells to commit to growth (Figure 8). Intriguingly, this correlation of tRNA thiolation with growth and rewired metabolism is emerging in cancer development (McMahon and Ruggero, 2018; Rapino et al, 2018), suggesting possibly conserved metabolic roles for these modified tRNAs.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, protein aggregation in the absence of U 34 modification is not limited to the yeast model system but was also observed in nematodes, mice and human cells [27,32,33,70,144,145]. In addition, the absence of the mitochondria-specific taurine-derived wobble uridine modifications induce aggregation of mistargeted mitochondrial proteins [146].…”
Section: A Role Of Protein Aggregation In Neurodegenerationmentioning
confidence: 99%
“…In support of this, it was already demonstrated that a conditional ELP3 knockout in mice induced the unfolded protein response (UPR) and caused reduced numbers of cortical projection neurons, leading to neurodevelopmental defects and microcephaly [144]. While UPR induction in tRNA modification mutants seems to be confined to higher eukaryotic cell systems, aggregation of endogenous cytoplasmic proteins is observed in both mammals and yeast cells [27,32,33,70,144,145,147].…”
Section: A Role Of Protein Aggregation In Neurodegenerationmentioning
confidence: 99%
“…Collectively, our study reveals how tRNA thiolation appropriately regulates metabolic outputs by controlling phosphate homeostasis, thereby enabling cells to commit to growth (Fig 7). Intriguingly, this correlation of tRNA thiolation with growth and rewired metabolism is now emerging in cancer development (McMahon and Ruggero, 2018; Rapino et al , 2018), suggesting possibly conserved metabolic roles for these modified tRNAs.…”
Section: Discussionmentioning
confidence: 99%